Foundations of Personal Fitness : Any Body Can-- be Fit! - Rainey, Don.; Murray, Tinker Dan, 1951- (Minneapolis/St. Paul : West Pub. Co., 1997)
Discusses the foundations of physical fitness, the benefits of regular exercise, and the advantages of weight training and proper nutrition.
Includes index.
Keywords: Physical fitness -- Health aspects -- Juvenile literature; Exercise -- Physiological aspects -- Juvenile literature; Health -- Juvenile literature; Physical fitness; Exercise; Health